PENGARUH METODE READING GUIDE BERBANTUAN MEDIA FLIPBOOK TERHADAP PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Nuroh, Rofatan; Indah Nurmahanani; Primanita Sholihah Rosmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the reading guide method assisted by flipbook media on improving reading comprehension skills of elementary school students. The low level of students' reading comprehension ability serves as the background for this research, which seeks to offer a more effective and engaging learning alternative. The research employed a quasi-experimental method with a non-equivalent control group design. The subjects were two fourth-grade classes at SDN Setia Mulya 02 in Bekasi Regency: the experimental class received instruction using the reading guide method assisted by flipbook media, while the control class used the cooperative learning model of the jigsaw type. Data collection techniques included pre-tests, post-tests, observation sheets, and documentation. The results of data analysis indicated a significant improvement in reading comprehension skills among students in the experimental class compared to the control class. It can be concluded that the reading guide method supported by flipbook media is effective in enhancing elementary students' reading comprehension skills.